Risk of major adverse limb events in patients with type 2 diabetes mellitus receiving sodium glucose cotransporter 2 inhibitors and glucagon-like peptide-1 receptor agonists: A population-based retrospective cohort study - Lee, Yen-Chieh; Dong, Yaa-Hui; Yang, Wei-Shun; Wu, Li-Chiu; Lin, Jou-Wei; Chang, Chia-Hsuin (Frontiers in Pharmacology, 2022)
Background Both sodium glucose cotransporter 2 inhibitors (SGLT-2i) and glucagon-like peptide-1 receptor agonists (GLP-1RA) have cardiovascular protective effects in type 2 diabetic patients. However, the comparative risk of GLP-1RA versus SGLT-2i for major adverse limb events in real-world practice remains unknown. Materials and Methods We studied a nationwide cohort involving 123,048 diabetes patients 20 to 100 years of age who initiated a SGLT-2i or GLP-1RA during 2012 and 2017. Incidence rates for hospitalization for major adverse limb event, critical limb ischemia (CLI) and lower extremity amputation (LEA), were assessed and hazard ratios (HRs) among patients receiving SGLT-2i as compared with GLP-1RA use were estimated by means of Cox proportional hazards regression after propensity score (PS) matching. We also examined if there is effect modification by age, a history of established cardiovascular disease or chronic kidney disease. Use of dipeptidyl peptidase-4 inhibitor (DPP-4i) was chosen as a second active comparator. Results A total of 26,756 PS-matched diabetes patients who initiated SGLT-2i and GLP-1RA were identified. Use of SGLT-2i was not associated with a significantly higher risk of hospitalized CLI and LEA (HR, 1.13; 95% CI, 0.77-1.65 and 1.27; 95% CI, 0.63-2.55 respectively). Also, no altered risks of CLI and LEA were found for SGLT-2i users when compared with DPP-4i use (HR,1.06; 95% CI, 0.75-1.50 and HR, 0.80; 95% CI, 0.42-1.53 respectively). Although the study was underpowered to explore potential effect modification by patients’ baseline characteristics, a trend of higher risks for LEA were noted among SGLT-2i users with cardiovascular disease as compared with either GLP-1RA or DPP-4i. Conclusions Use of SGLT-2i was not associated with higher risks for hospitalization for CLI and LEA as compared with GLP-1RA use. Further large-scale studies are needed for a precise risk estimation.